Konstribusi Kemampuan Manajerial Kepala Sekolah, Supervisi Akademik, Komitmen dan Motivasi Kerja Terhadap Kinerja Guru di SMK Negeri 5 Denpasar - S. Rejeki; I.P.W. Ariawan; I.M. Yudana (Pascasarjana Universitas Pendidikan Ganesha, 2023)
This study aims to 1) determine the contribution of managerial ability to teacher performance at SMK Negeri 5 Denpasar, 2) determine the contribution of academic supervision to teacher performance at SMK Negeri 5 Denpasar, 3) determine the contribution of work commitment to teacher performance at SMK Negeri 5 Denpasar, 4) to determine the contribution of work motivation to teacher performance at SMK Negeri 5 Denpasar, 5) to determine the contribution of principal managerial abilities, academic supervision, commitment and work motivation to teacher performance at SMK Negeri 5 Denpasar. This research is a survey research using a quantitative approach. The population in this study were all school principals and teachers at SMK Negeri 5 Denpasar, totaling 95 people. The research sample is the Krejci and Morgan formula, and the number of pieces is 76 people. Data collection using a questionnaire. The collected data were analyzed using simple, multiple, and partial regression techniques. The results of the study show that (1) there is a significant contribution between the managerial abilities of the principal and teacher performance at SMK Negeri 5 Denpasar with a practical contribution of 9.24%, (2) there is a significant contribution between academic supervision and teacher performance at SMK Negeri 5 Denpasar with a practical contribution of 9.05%, (3) there is a significant contribution between work commitment and teacher performance at SMK Negeri 5 Denpasar with a practical contribution of 8.36%, (4) there is a significant contribution between academic supervision and teacher performance at SMK Negeri 5 Denpasar with a practical contribution of 36.10%, and (5) the results of this study show a significant relationship between the managerial abilities of school principals, academic supervision, commitment, and work motivation together with teacher performance.